(untitled) (American Journal of Economics and Business Innovation, 2025)
Transparency, Security, efficiency; those three words can be assimilated to the fundamentals of a foreign operations, and that parties are all always in the obligation to optimise the process to fulfill their needs, this technology was reputed one of the valuable assets that appeared in the recent years was the blockchain technology gaining popularity in the financial world that we can emerge to the international trade offering a lot benefits. This research gives introduction about an innovative approach aimed at overcoming the limitations associated with reliance on stakeholders in international trade transactions. and it aims to add a valued solutions and to enhance the important gap existing research both conceptual foundations and practical insights . Moreover, we provide in our empirical part a study by VOSviewer, that it is enhance by The Methodi Ordinatio technique has been employed in this study to identify the most relevant studies in the field of international trade, guiding the research process through the selection, analysis, and systematic review of 42 articles retrieved from the Scopus database, all related to foreign trade transactions., to furnish a deeper perspective on the working of the mechanism By analyzing and identifying the highlight of the significant impact of blockchain on various trade-related processes.